2007
DOI: 10.5694/j.1326-5377.2007.tb01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and automatic reporting of estimated glomerular filtration rate: revised recommendations

Abstract: Since publication of the Australasian Creatinine Consensus Working Group's position statement in 2005, most Australasian laboratories now automatically report an estimated glomerular filtration rate (eGFR) (based on the Modification of Diet in Renal Disease [MDRD] formula) with results of serum creatinine tests in adults. Anecdotal evidence suggests that automatic reporting of eGFR helps to identify asymptomatic kidney dysfunction at an earlier stage and to develop rational and appropriate management plans. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 10 publications
1
82
0
Order By: Relevance
“…It was found that eGFR values fell with age, and this has also been previously observed 18. This may also be related to the fact that the population used for the derivatisation of the MDRD formula was aged <70 years 5.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It was found that eGFR values fell with age, and this has also been previously observed 18. This may also be related to the fact that the population used for the derivatisation of the MDRD formula was aged <70 years 5.…”
Section: Discussionsupporting
confidence: 72%
“…A higher proportion of women in the older age groups were included in the review. It has been recognised that reduced but stable eGFR values in individuals aged 70+ years may be accepted as typical for this age and may therefore not be associated with CKD complications,18 although this is not consistent with the UK CKD guidance 4…”
Section: Discussionmentioning
confidence: 95%
“…Despite the limitations, serum creatinine-based formulas are routinely used in daily clinical practice [1417]. In this paper, we will discuss approaches on how to use serum creatinine-based formulas in daily clinical practice in a well-informed way.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recommended dose changes for most drugs are crude (e.g., halving the dose or changing from twice-a-day regimen to a once-a-day regimen) [14]. One could argue that differences between eGFR and the true GFR will remain without practical consequences as long as they do not result in different renal function categories.…”
Section: Introductionmentioning
confidence: 99%
“…The Scottish Intercollegiate Guideline Network guidelines are broadly similar. 6 The UK guidelines, in common with US, 7 Australian, 8 and international 9 recommendations, all endorse the use of the simplified MDRD equation for estimation of GFR. Together these developments are designed to improve recognition and management of chronic kidney disease, which is expected to reduce the growth in the number of patients requiring renal replacement therapy and those presenting needlessly late in the course of their disease.…”
Section: Strategic Purpose Of Estimating Gfrmentioning
confidence: 99%